1988
DOI: 10.1182/blood.v71.3.717.717
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer into hematopoietic progenitor cells from normal and cyclic hematopoietic dogs using retroviral vectors

Abstract: The Moloney murine leukemia retrovirus-derived vector N2 was used to transfer the bacterial NeoR gene (conferring resistance to the neomycin analogue G418) into hematopoietic progenitor cells. Approximately 5% of day seven CFU-GM were resistant to 2,000 micrograms/ml G418, using a supernatant infection protocol in the absence of vector-producing cells. A greater proportion of CFU-GM colonies were recovered relative to uninfected controls as the stringency of selection was diminished. Enzyme activity was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Inhibition of HIV replication in varying degrees by antisense RNA as well as sense RNA has been shown [15,26,29]. We now report that using a murine retroviral vector [10,11,13], an anti-SIV gene can be efficiently delivered into a cultured human CD 4 + cell line in which it can effectively block SIV and HIV replication. This report represents the first step towards the application of antisense/sense gene therapy approach in an animal model.…”
Section: Introductionmentioning
confidence: 89%
“…Inhibition of HIV replication in varying degrees by antisense RNA as well as sense RNA has been shown [15,26,29]. We now report that using a murine retroviral vector [10,11,13], an anti-SIV gene can be efficiently delivered into a cultured human CD 4 + cell line in which it can effectively block SIV and HIV replication. This report represents the first step towards the application of antisense/sense gene therapy approach in an animal model.…”
Section: Introductionmentioning
confidence: 89%
“…Cocultivation of amphotropic producer cells with canine bone marrow cells [29,30] resulted in approximately 40% provirus positive CFU-GM as established by drug resistance. In contrast, only 5% drug resistant CFU-GM were scored using supernatant transduction [31]. These initial experiments indicated that, similar to the murine situation, cocultivation was superior to supernatant transduction.…”
Section: Gene Therapy Studies In Nonhuman Primates and Humansmentioning
confidence: 99%
“…Several studies have recently demonstrated that a foreign gene can be transferred into murine (2, 10,11,13,15,23,24,27,28,40), canine (16,38), primate (4,22), or human (25) hematopoietic progenitors and stem cells by using retroviral vectors. This technology holds promise for potential somatic cell genetic therapy, or it could be a powerful tool for analyzing the dynamics of somatic cells such as hematopoietic cells.…”
mentioning
confidence: 99%